A malignant placental site trophoblastic tumor of the uterus with multiple metastases: A case report of a rare tumor showing an aggressive behavior - Amany Abdulgader Fathaddin; Maria Abdulrahim Arafah (Wolters Kluwer Medknow Publications, 2019)
One of the very rare forms of gestational neoplastic diseases is the malignant placental site trophoblastic tumor. Due to its rarity, the data regarding its diagnosis and management are limited. The prognosis of this tumor is unpredictable with potential malignant behavior and metastasis. We report a case of malignant placental site trophoblastic tumor with multiple metastatic deposits in the ovaries, lungs, kidneys, adrenals, and pancreas. The patient was treated by surgery and an extensive subsequent chemotherapy. The disease progressed, and the patient died 17 months after diagnosis.